How does economic policy uncertainty affect corporate debt maturity? - Xiang Li (Halle Institute for Economic Research (IWH), 2022)
This paper investigates whether and how economic policy uncertainty affects corporate debt maturity. Using a large firm-level dataset for four European countries, we find that an increase in economic policy uncertainty is significantly associated with a shortened debt maturity. Moreover, the impacts are stronger for innovation-intensive firms. We use firms' flexibility in changing debt maturity and the deviation to leverage target to gauge the causal relationship, and identify the reduced investment and steepened term structure as the transmission mechanisms.
Keywords: D81; G32; 330; capital structure; corporate investment; debt maturity; economic policy uncertainty